Burn Injury Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Rat Gastrointestinal Microbiome - Huang, Guangtao; Sun, Kedai; Yin, Supeng; Jiang, Bei; Chen, Yu; Gong, Yali; Chen, Yajie; Yang, Zichen; Chen, Jing; Yuan, Zhiqiang; Peng, Yizhi (Frontiers in Microbiology, 2017)
The gastrointestinal microbiome is crucial in human health. With greater than 10 times the cell count of an individual, the gastrointestinal microbiome provides many benefits to the host. It plays an important role in chronic illnesses and immune diseases and also following burns and trauma. This study aimed to determine whether severe burns affect the gastrointestinal microbiome during the early stages of after burn injury and the extent to which the microbiome is disturbed by such burns. We used a rat burn model to investigate any changes occurring in the microbiome after the burn trauma using 16S rRNA sequencing and downstream α-diversity, β-diversity, and taxonomy analysis. With 128631 and 143694 clean sequence reads, an average of 2287 and 2416 operational taxonomic units (OTUs) were recognized before and after the burn injury, respectively. Bacterial diversity within the pre- and post-burn groups was similar according to OTU richness, Chao 1 index, Shannon index and ACE index. However, the constituents of the gastrointestinal microbiota changed after the burn injury. Compared with the pre-burn samples, the post-burn samples showed a tendency to cluster together. The ratio of Firmicutes to Bacteroidetes decreased after the burn injury. Also, the abundance of some probiotic organisms (i.e., butyrate-producing bacteria and Lactobacillus) decreased after the burn injury. In contrast, opportunistic pathogenic bacteria, such as those of the genera Escherichia and Shigella and the phylum of Proteobacteria are more abundant post burn. In conclusion, dysbiosis in the gastrointestinal microbiome was observed after the burn injury. Although the total number of species in the gastrointestinal microbiome did not differ significantly between the pre- and post-burn injury groups, the abundance of some bacterial components was affected to various extents.